2019
DOI: 10.1177/0084672419883339
|View full text |Cite
|
Sign up to set email alerts
|

Doctor–patient communication about existential, spiritual and religious needs in chronic pain: A systematic review

Abstract: Research documents that many chronic non-malignant pain patients experience existential, spiritual and religious needs; however, research knowledge is missing on if and how physicians approach these needs. We conducted a systematic review to explore the extent to which physicians address these needs in their communication with chronic non-malignant pain patients and to explore the facilitators and challenges of this communication. We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…They suggest that for some patients such underlying issues must be addressed if motivation to use and benefit from eHealth intervention is to be expected. These results may argue for blended care where the eHealth intervention could supplement communication with the health care provider where active listening and acknowledgement of existential concerns might be essential [ 69 ]. Adding guidance and personal feedback is also a way of tailoring the intervention [ 70 ], as suggested in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…They suggest that for some patients such underlying issues must be addressed if motivation to use and benefit from eHealth intervention is to be expected. These results may argue for blended care where the eHealth intervention could supplement communication with the health care provider where active listening and acknowledgement of existential concerns might be essential [ 69 ]. Adding guidance and personal feedback is also a way of tailoring the intervention [ 70 ], as suggested in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our study suggests that attending to existential, spiritual, and religious needs in the encounter requires a relation with the possibility of addressing both conscious and unconscious needs from a personal, empathic perspective. Moreover, this relational approach seems to be pivotal for treatment of chronic illnesses (Andersen, Assing Hvidt, Hvidt, & Roessler, 2019 ; Vang et al, 2019 ) and even more so in countries with a cultural experience of privacy regarding these needs (Assing Hvidt, Søndergaard, et al, 2017 ; Rosen, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…The three co-authors are all experienced researchers in the field of existential communication in medicine. Existential communication covers how health professionals communicate with patients about the diverse ways to make meaning in life, whether secular, spiritual, or religious (Andersen, Assing Hvidt, Hvidt, Illés, et al, 2019 ; Andersen, Assing Hvidt, Hvidt, & Roessler, 2019 ; Assing Hvidt, Hansen, et al, 2017 ; Roessler & Lindemann, 2014 ). Their prior understandings regarding the use of IPA and the selected themes have informed and enhanced this study and been a subject of discussion between all authors in the research process.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although research has shown that faith is a legitimate human expression that influences health, healthcare personnel seemed reluctant to approach these needs (Dezutter et al 2016;Assing Hvidt et al 2016;Andersen et al 2019). This may have been due to a lack of knowledge and/or training, as well as an apprehension regarding imposing their own meaning system on the patients Mueller et al 2001;Best et al 2016).…”
Section: Introductionmentioning
confidence: 99%